2010
DOI: 10.1021/je901070e
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Lead Ions by Hydroxyapatite Prepared from the Egg Shell

Abstract: Carbonate hydroxyapatite (CHAP) was synthesized from domestic hen egg shells. The obtained CHAP was characterized by X-ray diffraction (XRD) and Fourier transform infrared spectroscopy and investigated as metal adsorption for Pb 2+ from aqueous solutions. The effect of various parameters on the adsorption process such as contact time, solution pH, and temperature was studied to optimize the conditions for maximum adsorption. The results showed that the removal efficiency of Pb 2+ by carbonate hydroxyapatite ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(53 citation statements)
references
References 40 publications
1
50
0
Order By: Relevance
“…Nanoparticles (NPs) have high potential for the tertiary wastewater treatment technology because of their small size (1-100 nm), catalytic potential, highly reactive and large surface area, ease of separation, large number of active sites, and regeneration ability (Ali 2012). Hydoxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 ) is an ideal adsorbent because of its high sorption capacity for heavy metals, low water solubility, easy availability, low cost, and applicability under oxidizing and reducing conditions (Meski et al 2010;Ramesh et al 2012). Recently, Tang et al (2013) reported removal of Cr(VI) from aqueous solution using hydroxyapatite nanoparticles (HANPs) of different Ca/P ratios.…”
mentioning
confidence: 99%
“…Nanoparticles (NPs) have high potential for the tertiary wastewater treatment technology because of their small size (1-100 nm), catalytic potential, highly reactive and large surface area, ease of separation, large number of active sites, and regeneration ability (Ali 2012). Hydoxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 ) is an ideal adsorbent because of its high sorption capacity for heavy metals, low water solubility, easy availability, low cost, and applicability under oxidizing and reducing conditions (Meski et al 2010;Ramesh et al 2012). Recently, Tang et al (2013) reported removal of Cr(VI) from aqueous solution using hydroxyapatite nanoparticles (HANPs) of different Ca/P ratios.…”
mentioning
confidence: 99%
“…From the first order rate equation the value of regression coefficient (R 2 ) is in between (0.91-0.99) which is closer to 1 and shows best agreement with literature. Energy of activation was calculated from Arrhenius straight line equation [27] which is as follows: ln (9) and are rate constants, is the activation energy, R is gas constant and T is absolute temperature. The activation energies calculated for acid adsorbed on raw and treated powder egg shells are given in Table 4.…”
Section: Adsorption Kinetic Linear Equationsmentioning
confidence: 99%
“…Because of high cost and disposal problems, many of the conventional methods have not been applied at large scale in different industries. Adsorption has been found to be superior to other techniques in terms of low-cost, flexibility and simplicity of design, ease of operation and insensitivity to toxic pollutants [9] . In adsorption, different adsorbents used include activated carbon [10] , zeolite [11] , clays [12] , silica beads [13] , and polymeric acids [14] etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Nowadays, the research studies have been focused on nanohydroxyapatite (n-HAp) because of its high surface area and reactivity. 10 However, the application of n-HAp in adsorption columns is limited because of its powder form, insufficient strength, and brittleness.…”
mentioning
confidence: 99%